The Role of Gamification in English Language Teaching: Insights from Pre-Service Teachers (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Gamification has emerged as an innovative approach to English language teaching, aiming to enhance student engagement and motivation. This study investigates pre-service teachers' perceptions of gamification in English language teaching practice. This study employed a mixed method based on an explanatory-sequential design as qualitative can clarify generalized quantitative results in a more thorough and appropriate interpretation. The study began by gathering quantitative data through a Likert scale questionnaire, followed by collecting qualitative data through semi-structured interviews with 100 pre-service teachers from Universitas Brawijaya post-teaching practice. The findings show that most pre-service teachers perceive gamification in English language teaching positively. Specifically, 89% of respondents reported increased engagement, while 85% noted improved motivation and focus. However, 15% of respondents remained ambivalent about how well gamification encourages self-directed learning. Additionally, 87% of respondents plan to continue using gamification in their teaching. In conclusion, gamification has the potential to be an innovative pedagogical approach in English language teaching, not only by enhancing engagement and motivation but also by facilitating differentiated learning by enabling students to gain the material at their own pace and fostering an immersive learning environment that enhances language acquisition. However, some challenges, such as limited infrastructure and pre-service knowledge and readiness to implement learning technology still need to be improved. Therefore, this study provides recommendations for educational institutions that can support the optimization of gamification in the context of English language teaching in the future. Further studies could explore its long-term effects on language learning to better understand its sustained impact.